2016
DOI: 10.1111/jne.12444
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Maternal Exposure and Foetal Sex Determine the Effects of Low‐level Chemical Mixture Exposure on the Foetal Neuroendocrine System in Sheep

Abstract: We have shown that continuous maternal exposure to the complex mixture of environmental chemicals (ECs) found in human biosolids (sewage sludge), disrupts mRNA expression of genes crucial for development and long-term regulation of hypothalamic-pituitary gonadal (HPG) function in sheep. The present study investigated whether exposure to ECs only during preconceptional period or only during pregnancy perturbed key regulatory genes within the hypothalamus and pituitary gland and whether these effects were differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 62 publications
(82 reference statements)
0
6
0
Order By: Relevance
“…In fact, recent reports highlighted that environmental pollution and climate change are significantly increasing the risk of birth defects, especially after prolonged exposure [147,148]. Indeed, it has been proposed that timing and duration of maternal exposure to a complex mixture of environmental chemicals impairs the fetal neuroendocrine system in a sex-specific manner, as expression of some genes involved in neuroendocrine development is altered in male fetus in comparison with control [149].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, recent reports highlighted that environmental pollution and climate change are significantly increasing the risk of birth defects, especially after prolonged exposure [147,148]. Indeed, it has been proposed that timing and duration of maternal exposure to a complex mixture of environmental chemicals impairs the fetal neuroendocrine system in a sex-specific manner, as expression of some genes involved in neuroendocrine development is altered in male fetus in comparison with control [149].…”
Section: Discussionmentioning
confidence: 99%
“…While ATSDR includes studies in other laboratory mammal species, the vast majority of the toxicological database is focused on these two species. Studies utilizing sheep have shown that exposure to environmental chemicals prior to conception only, during pregnancy only, or throughout life can affect the developing fetus differently (Bellingham et al 2009, 2016; Lea et al 2016). These results support findings in rodents.…”
Section: Discussionmentioning
confidence: 99%
“…Specific hypothalamic areas were isolated for RNA extraction as described previously. 52 Briefly, the hemi-hypothalamic block was cut into 2 mm coronal slices, and relative to visible anatomical landmarks (the anterior commissure, the mammillary body, etc. ), 2 mm diameter punches representative of specific hypothalamic areas collected into TRIzol ® reagent (Invitrogen, Carlsbad, CA, USA).…”
Section: Harvest and Processing Of Metabolismrelated Tissuesmentioning
confidence: 99%